Biochemical Evaluation of Cotton Genotypes using Soluble Protein, Esterase (EST), Peroxidase (POX) And Polyphenol Oxidase (PPO) and their Role in Plant Disease Resistance - Ujjainkar, V.V.; Patil, V.D.; Mane, S.S.; Moharil, M.P. (Journal for Research in Applied Sciences and Biotechnology, 2022)
Isozyme analysis is a powerful biochemical technique that has numerous applications in plant biology. It has long been used by geneticists to study the population genetics. The isozyme esterase, peroxidase and polyphenol oxidase were standardized for upland cotton (Gossypium hirsutum L.) germplasm lines collected from all over the country. The knowledge of nature and magnitude of genetic diversity present in the germplasm is most important pre-requisite for the success of any breeding program. The thirty-four cotton germplasm lines were screened for prime three isozymes based on quantification assay and qualitative PAGE profiling. Among the material, the genotype AKH – 24 (190.60 mg ml-1), AKH – 053 (189.42 mg ml-1) and VIKAS (184.53 mg ml-1) recorded high protein content, whereas the enzymatic activities of esterase, peroxidase and polyphenol oxidase exhibited remarkable differences along with the protein content. The genotype LRA–5166 exhibited high esterase (462.68 mM mg protein-1 min-1) and peroxidase activity (250.97mM mg protein-1 min-1), while AKH – 24 recorded the maximum polyphenol oxidase activity (131.45 mM mg protein-1min-1). The banding pattern of biochemical markers revealed that the maximum number of bands were recorded in esterase analysis (fifteen) followed by protein (twelve) whereas, only five bands each were detected in peroxidase and polyphenol oxidase analysis indicating limited polymorphism. The Relative Mobility (Rm) values were ranged from 0.083 to 0.883 (protein), 0.100 to 0.971 (esterase), 0.033 to 0.283 (peroxidase) and 0.048 to 0.206 (polyphenol oxidase). The present study demonstrated that cotton genotypes could be differentiated by their quantity and quality through electrophoretic banding profiles. These results could be of practical value for cultivar identification, purity testing along with associated prediction of pest and disease resistance. However, the major constraint is that these biochemical markers do not able to reproduce the similar kind of variation pattern, but can provide strong distinguishing polymorphism each time.